Teachers’ Strategies to Address Picky Eating in Indonesian PAUD Classrooms: A Sequential Explanatory Mixed-Methods Study - Efi Yulistiani; Diana Diana; Deni Setiawan (AL-ISHLAH: Jurnal Pendidikan, 2025)
Picky eating is a common issue among preschool children, potentially impacting their nutritional status and development. This study aimed to examine teacher-led strategies in addressing picky eating behaviors among children aged 4–6 years in early childhood education (PAUD) settings in the Mawar Cluster, Moga District, Indonesia. A sequential explanatory mixed-methods design was employed. Quantitative data were collected from 36 identified picky eaters through anthropometric measurements (BAZ) at baseline and after a 12-month school-based supplementary feeding program (PMTAS). Additional data included responses from 14 teachers and 36 parents using the Children’s Eating Behaviour Questionnaire (CEBQ). Qualitative data were gathered via interviews, classroom observations, and documentation, and analyzed thematically. The proportion of children with normal nutritional status increased from 86.1% to 91.6%, with improvements noted in undernutrition and overweight cases. Teachers employed strategies such as integrating nutrition education into thematic learning (e.g., songs, role-play), creative food presentation, communal eating routines, and close collaboration with parents. These efforts were reinforced at home through adapted lunchbox practices and consistent communication. The integration of pedagogical approaches with parental involvement effectively improved children’s food acceptance and nutritional outcomes. The findings support the importance of structured, enjoyable, and collaborative strategies in addressing picky eating in PAUD settings. These results offer practical implications for teacher training and the enhancement of school-based nutrition interventions in early childhood education.